PENGELOLAAN SAMPAH KOTA PEKANBARU - Rielasari, Irienda; Rusli SD, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Waste is a wasted or intentionally disposed material derived from the results of human and natural activities that do not have economic value. Pekanbaru city is one of the city that does not escape from garbage problem. The waste management of Pekanbaru City includes the final collection, collection, transportation, processing and disposal. Current waste management has not solved the problem optimally. The concept of waste management conducted by urban community Pekanbaru at this time mostly only in the context of transporting waste from waste sources to landfills (TPA) which then will have an impact on the environment and health around the TPS are supported also with the behavior of people who are still mixing between dry waste and wet garbage. Type of research is done by qualitative approach with descriptive method. Based on field facts with data collection techniques include observation, interviews, documentation studies related to research objectives.The results of research conducted by researchers can be concluded that waste management Pekanbaru not yet maximal, this is based on the concept of waste management that is still not running optimally to change the old waste management concept to the new management concept using 3R concept (reduce, reuse and recycle) conducted by the government. This is influenced by the lack of public awareness and kuranngnya infrastructure facilities as a tool in the process of waste management.Keywords : Waste, Waste Management, Integrated Management